The roar of the crowd - Wallace, Rich. (New York : Viking, 2004)
After years of playing nothing but soccer in Hudson City, New Jersey, Manny has to work very hard to play on the middle school football team, using determination, speed, and smarts to make up for being small and inexperienced.
Keywords: Football; Self-confidence; Sportsmanship